Bacillus As Potential Probiotics: Status, Concerns, and Future Perspectives - Elshaghabee, Fouad M. F.; Rokana, Namita; Gulhane, Rohini D.; Sharma, Chetan; Panwar, Harsh (Frontiers in Microbiology, 2017)
Spore-forming bacilli are being explored for the production and preservation of food for many centuries. The inherent ability of production of large number of secretory proteins, enzymes, antimicrobial compounds, vitamins, and carotenoids specifies the importance of bacilli in food chain. Additionally, Bacillus spp. are gaining interest in human health related functional food research coupled with their enhanced tolerance and survivability under hostile environment of gastrointestinal tract. Besides, bacilli are more stable during processing and storage of food and pharmaceutical preparations, making them more suitable candidate for health promoting formulations. Further, Bacillus strains also possess biotherapeutic potential which is connected with their ability to interact with the internal milieu of the host by producing variety of antimicrobial peptides and small extracellular effector molecules. Nonetheless, with proposed scientific evidences, commercial probiotic supplements, and functional foods comprising of Bacillus spp. had not gained much credential in general population, since the debate over probiotic vs pathogen tag of Bacillus in the research and production terrains is confusing consumers. Hence, it’s important to clearly understand the phenotypic and genotypic characteristics of selective beneficial Bacillus spp. and their substantiation with those having GRAS status, to reach a consensus over the same. This review highlights the probiotic candidature of spore forming Bacillus spp. and presents an overview of the proposed health benefits, including application in food and pharmaceutical industry. Moreover, the growing need to evaluate the safety of individual Bacillus strains as well as species on a case by case basis and necessity of more profound analysis for the selection and identification of Bacillus probiotic candidates are also taken into consideration.